Novel cool roofing technology system with sustainable design for attic temperature reduction - Mun Ling Ho; Ming Chian Yew; Ming Kun Yew; Lip Huat Saw; Weng Cheong Tan; Richard Kwok Kit Yuen (Ain Shams Engineering Journal, 2024)
The penetration of increasing solar gain towards the building deteriorates the building's thermal quality and raises cooling demand. In particular, the roof receives the most solar gain. The roof system reformation is urged to improve the roof system's heat capacity and conserve building energy. This paper introduced a novel cool roofing system to replace the traditional roof system. The proposed novel cool roofing applications merged: (i) lightweight foam concrete, (ii) hollow concrete slab, (iii) white cooling paint and (iv) active reflective insulation system powered by solar energy. The discovery of the proposed system was evaluated with experimental chambers exposed to the outdoor environment. Under intense sunlight, the internal roof surface was 30.6 % cooler (50.5 °C to 35.0 °C). The mean attic temperature achieved was 33.9 °C under a field where the daily maximum recorded surrounding temperature is 43.0 °C. In contrast with a bare roof at 41.9 °C, the proposed design demonstrated a 19.2 % lower solar gain, achieving a sub-ambient structure. Besides that, the cooling demand simulation generated similar cooling demand savings (20 %). Significantly, this comprehensive cool roofing system exhibited a considerable and constructive outcome in cooling the buildings by achieving sustainable development to create a better and more environmental future for all.